Metodologias para a determinação de perdas endógenas de fósforo para suínos em crescimento - Alves, Débora Aline (2015)
Phosphorus (P) is essential for swine and must be supplied in adequate amounts in order to minimize the costs of production and to reduce environmental impact. The standardized digestibility is a good estimate of available P on feedstuffs. To determine the standardized total tract digestibility of P (STTD) it is necessary to know the endogenous losses of P (ELP). The P-free diet is a methodology largely utilized to find ELP. Gelatin (GEL) is the elected protein source to formulate a P-free diet in most trials around the world. In Brazil, however, spray dried plasma (SDP) has been utilized as a protein source in P-free diets. In spite of small content and high digestibility of P present in SDP, its use may lead to incorrect values of ELP and, as a consequence, overestimation of the standardized digestibility coefficients of P in feedstuffs for pigs. However, one of the advantages of SDP use is the small cost in relation to GEL and, for this reason, more studies on the influence of SDP on ELP and P digestibility are justified. Therefore, a trial was carried out to compare the ELP in swine fed diets containing GEL or SDP as a protein source and to determine the STTD in SDP. The study was developed at the Swine Farm of the Federal University of Santa Maria Brazil. A total of 12 castrated pigs with average initial weight of 55 kg were individually allotted to metabolic crates. The trial was developed in two 12-days periods, with 7 days of adaptation and 5 days of total fecal collection. The beginning and the end of the collection were determined according to the marker-to-marker approach, using ferric oxide as an indigestible marker. Pigs were weighed at the start and at the end of adaptation period and at the end of collection. The treatments were four semi-purified diets. One of them had a P-free diet with 30% of GEL as the only protein source. The other three treatments had 10, 20 and 30% inclusion of SDP. A 1:1 Ca to P ratio was used for all diets. Data were subjected to ANOVA and the model included the effects of period, animal and treatments. Then, the results of the three diets with increased levels of SDP were subjected to linear regression analysis. The intercept of the relation of ingested P and absorbed P represented the endogenous losses of P. The slope indicated the STTD of SDP. The ELP means obtained by P-free diet and regression method were compared with the Student t test. The ELP were 128.95 mg/kgDMI and 153 mg/kgDMI (SE = 77.0; P<0.06) using the P-free diet with GEL as the protein source and the regression method, obtained with diets containing increased levels of SDP, respectively. The apparent digestibility of P was 87.9, 94.2 and 92.9% for the treatments containing 10, 20 and 30% inclusion of P, respectively. The estimated STTD obtained with the linear regression was 97.4%. The corrected values of apparent digestibility of P, obtained with the diets containing SDP, using the basal endogenous loss estimated by the P-free diet, were 96.9, 98.8 and 95.9% for 10, 20 and 30% of SDP, respectively. Therefore, it can be concluded that SDP can replace GEL as a source of protein (amino acids) in P-free diets to estimate the endogenous losses of P. In addition, the standardized digestibility of P in SDP estimated with the P-free diet with GEL as the protein source was 97.2% and it was 97.4% obtained by the regression method, utilizing SDP as the source of protein.